DESTINATION IMAGE OF COCO CABANA, MIRI AMONG VISITORS - Wani Afrina, Hassdi; Shaik Azahar, Shaik Hussain
This study was conducted to find out the visitors' opinions about the destination image of Coco Cabana. This study also aims to study the facilities factor and to analyze the attraction factor on visitors' opinions about the destination image at Coco Cabana. In order to obtain data for this study, the researcher used quantitative methods by distributing questionnaires. A total of 384 respondents who have been to Coco Cabana were involved in answering the questionnaires.